2007
DOI: 10.2337/dc06-2338
|View full text |Cite
|
Sign up to set email alerts
|

Discordance in Perceptions of Barriers to Diabetes Care Between Patients and Primary Care and Secondary Care

Abstract: OBJECTIVE -We sought to compare perceived barriers to diabetes care between people with diabetes and different health professional groups. RESULTS -Barriers were reported in 69.7% of patients. Psychological barriers were most important (55.5%), followed by systems barriers (25.7%), and then knowledge as least important (15.3%). Psychological barriers were ranked first among general practitioners (91.0%), but systems barriers were ranked first by other health professionals (38.8 -100%). General practitioner and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
2
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 20 publications
3
67
2
5
Order By: Relevance
“…On a positive note we did not find an association between ethnicity and attendance at structured education, found in one US study [12], although we did broadly group participants into ethnic groups and qualitative research has demonstrated that some West Africans might be opposed to group education for fear of stigmatisation [18]. Overall, the findings contrast with patient-reported barriers to diabetes self-management, which have identified psychological and psychosocial barriers [13]. We found no association between selfreported depression, diabetes-related distress, or diabetes self-efficacy with attendance at structured education and there is no suggestion as to what the underlying mechanisms are which motivate people to attend.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…On a positive note we did not find an association between ethnicity and attendance at structured education, found in one US study [12], although we did broadly group participants into ethnic groups and qualitative research has demonstrated that some West Africans might be opposed to group education for fear of stigmatisation [18]. Overall, the findings contrast with patient-reported barriers to diabetes self-management, which have identified psychological and psychosocial barriers [13]. We found no association between selfreported depression, diabetes-related distress, or diabetes self-efficacy with attendance at structured education and there is no suggestion as to what the underlying mechanisms are which motivate people to attend.…”
Section: Discussioncontrasting
confidence: 67%
“…Well known barriers to optimal diabetes self-care include psychological and social factors [13] and low levels of health literacy may discourage attendance or prevent those affected from benefitting from this mode of self-management support [14][15][16][17]. Qualitative research of patient barriers to attending structured education programmes have identified: lack of information regarding DSME from health professionals, not perceiving the benefit of attendance, difficulties in access, and shame and stigma of diabetes [18].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, more emphasis has been placed on the training and education of clinicians rather than their attitudes and beliefs, but motivation of the health professionals is increasingly being recognized as having as central role in diabetes care (12). However, this finding must be approached with caution given the subjective nature of the term "motivation," even within the context of a theoretical model (30), and the subjective method of data collection (interviews and observations).…”
Section: Factors Associated With Improved Quality Of Carementioning
confidence: 99%
“…Commonly reported patient factors are adherence, attendance, and education together with individual characteristics such as age, sex, and presence of comorbidity (11)(12)(13)(14). Health physician factors include the number, training, and sex of the treating physician and practice team; the role of clinical inertia; and the clinician/ patient relationship (10,12,(15)(16)(17)(18). Many organizational factors have been shown to influence care such as the use of structured diabetes clinics, recall systems, practice guidelines, and educational programs (14,19).…”
mentioning
confidence: 99%
“…Although the prevention of morbidity and mortality of these cases seems simple, many patients with diabetes do not follow their physician’s self-care recommendations regarding diabetes. Although Iranian patients have little information about the average blood sugar control, the increasing diabetes prevalence is an alarm of the poor diabetes control among them (9, 10). Self-care improves the quality of life and also may reduce costs.…”
Section: Introductionmentioning
confidence: 99%